POTENSI LIMBAH KULIT KOPI SEBAGAI COMPLETE FEED YANG SESUAI UNTUK PAKAN TERNAK DOMBA - Eny Hari W Widowati; Surono Surono; Mary Cristanto; Edy Rianto (JURNAL LITBANG PROVINSI JAWA TENGAH, 2014)
Temanggung Regency is a center of coffee production with waste that has not been utilized to the optimum. In addition there are agricultural wastes that have the opportunity to be processed into animal feed. The experiment was conducted for 3 months in the village of Waterford County Tlahap Kledung Subdistrict. Objective: To analyze the potential of coffee as a complete feed leather feed. Methods : The study experiments using animal ram + 1 year of age with a body weight of 22-25 kg beginning with number 12 tails, fed complete feed 3 lambs and cattle fed a conventional form of fresh grass and tofu. The study design was completely randomized design ( CRD ) consisting of 4 treatments ( levels 0, 10, 20,30 % leather coffee fermentation in complete feed) were repeated 3 times. The results showed that coffee skin potential as animal feed in the form of complete feed formulated with pretreatment through fermentation to increase the crude protein, crude fat and lower fiber content, tannin and NDF her skin so that waste coffee can be done in the long term to feed livestock. The composition of the ration used was : 30 % Caucasian fermented coffee, corn Tebon 1 % , 1 % corn cobs, corn klobot 1 %, corn bran 11 %, 37 % weeds, remujung 1 %, red skin peanut pods 3 % and drops 15 %. The results of the study showed no significant differences ( P > 0.05 ) on feed intake, body weight gain, feed conversion and efficiency. Preparation of rations which provide improved daily body weight and feed efficiency in the use of the highest in the treatment of skin coffee as much as 30 % ( T3 ). The highest body weight gain in the treatment of skin use coffee as much as 30 % ( T3 ).